2015
DOI: 10.13189/ujer.2015.031208
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Deficits in Autism: A Study among Students with Austim Spectrum Disorder in Inclusive Classrooms

Abstract: Students with Autism Spectrum Disorder (ASD) who lack of social skills have been hindered from being included in IE classrooms. The purpose of this study was to identify the most frequently occurring social skills deficits area among students with ASD in IE classrooms so that the mainstream teachers will be ready and well prepared to cater to their special educational needs (SEN) accordingly in order to yield more effective educational outcomes. A total of 34 teachers in three schools with inclusive classrooms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
0
19
0
3
Order By: Relevance
“…Children with deficits in social skills are more likely to face impairments in social life, academic progress, and delayed early language and communication (Reichow, Volkmar, & Cicchetti, 2008). They also have difficulties in eye contact, joint attention, initiating and maintaining conversations, problem-solving ability, empathy, and interpreting body language (American Psychiatric Association (APA), 2013; Yeo & Teng, 2015). The training therefore focused on providing practicum students with social stories and play strategies, as well as on teaching turn-taking in conversation.…”
Section: Discussionmentioning
confidence: 99%
“…Children with deficits in social skills are more likely to face impairments in social life, academic progress, and delayed early language and communication (Reichow, Volkmar, & Cicchetti, 2008). They also have difficulties in eye contact, joint attention, initiating and maintaining conversations, problem-solving ability, empathy, and interpreting body language (American Psychiatric Association (APA), 2013; Yeo & Teng, 2015). The training therefore focused on providing practicum students with social stories and play strategies, as well as on teaching turn-taking in conversation.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with Cheung, Siu, Brown (2017), who found that persons with ASD may have difficulty in making friends as one of the assertive behavior, and total lack of facial expressions as one of the empathy skills. Yeo & Teng (2015), also suggested that ASD have social skills deficits fall under the areas of behavioral and affective. Students with autism are characterized by their social skills difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…They also identified that the symptoms as such repetitive activities, stereotyped movements, struggle to adapt in the environment and the daily routine and unusual responses to sensory experiences. Autism spectrum disorders (ASD) is characterized by social communication and social interaction (Yeo & Teng, 2015). Researcher mentioned that ASD restricted repetitive patterns of behavior, interests and activities.…”
Section: Characteristic Of Asdmentioning
confidence: 99%